Progression in Neuroimaging of Normal Pressure Hydrocephalus - Yin, Rui; Wen, Junxian; Wei, Junji (Frontiers in Neurology, 2021)
Normal pressure hydrocephalus (NPH) is a clinical syndrome that mainly targets elderly population. It features dementia, impaired walking, and malfunction of sphincters. Rapid identification and large-scale screening of those patients are of great significance as surgery interventions can greatly improve or even reverse the symptoms. This review aims to summarize traditional parameters used to diagnose NPH and emerging progression in neuroimaging of the disease, hoping to provide an up-to-date overall perspective and summarize the possible direction of future development.